The Synergy Effect: Managerial Competence and Work Motivation in Teacher Performance - Renny Octavia; Alhadi Yan Putra; Pahlawan Pahlawan (FKIP - Universitas Riau, 2026)
This study aims to analyze the influence of principals’ managerial competence and work motivation on teacher performance in senior and vocational high schools in Pemulutan District. Using a quantitative approach with an ex post facto design, the research involved 81 teachers through census technique. Data collection instruments consisted of validated Likert-scale questionnaires (r>0.374; α>0.90). Data analysis employed Spearman correlation and multiple linear regression. Based on the analysis, principals’ managerial competence has a positive and significant effect on teacher performance with a moderate contribution, while work motivation shows a stronger and more dominant positive influence with a higher contribution. Simultaneously, both variables significantly affect teacher performance with a strong combined contribution and a small synergistic effect. The regression equation further indicates that work motivation has a greater impact than managerial competence, making it the most influential factor in improving teacher performance. Managerial implications: principals need to optimize managerial competence while facilitating the development of teachers’ work motivation to enhance education quality.